Positivity in electron-positron scattering: testing the axiomatic quantum field theory principles and probing the existence of UV states *CZ is supported by IHEP (Y7515540U1) and National Natural Science Foundation of China (NSFC) (12035008). SYZ acknowledges support from the starting grants from University of Science and Technology of China (KY2030000089, GG2030040375) and is also supported by NSFC (12075233, 11947301, 12047502) and supported by the Fundamental Research Funds for the Central Universities (WK2030000036). This work has been supported by the FCPPL France China Particle Physics Laboratory of the IN2P3/CNRS. (February 2021) - Fuks, Benjamin; Liu 刘, Yiming 一鸣; Zhang 张, Cen 岑; Zhou 周, Shuang-Yong 双勇
Abstract: We consider the positivity bounds on dimension-8 four-electron operators and study two related phenomenological aspects at future lepton colliders. First, if positivity is violated, probing such violations will revolutionize our understanding of the fundamental pillars of quantum field theory and the S -matrix theory. We observe that positivity violation at scales of 1-10 TeV can potentially be probed at future lepton colliders even if one assumes that dimension-6 operators are also present. Second, the positive nature of the dimension-8 parameter space often allows us to either directly infer the existence of UV-scale particles together with their quantum numbers or exclude them up to certain scales in a model-independent way. In particular, dimension-8 positivity plays an important role in the test of the Standard Model. If no deviations from the Standard Model are observed, it allows for simultaneous exclusion limits on all kinds of potential UV-complete models. Unlike the dimension-6 case, these limits apply regardless of the UV model setup and cannot be removed by possible cancellations among various UV contributions. This thus consists of a novel and universal test to confirm the Standard Model. We demonstrate with realistic examples how all the previously mentioned possibilities, including the test of positivity violation, can be achieved. Hence, we provide an important motivation for studying dimension-8 operators more comprehensively.